Clusters of Brazilian municipalities and the relationship with their fiscal management - Afonso, Marcio; Escovedo, Tatiana (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The management of municipal finances is crucial in providing quality services and infrastructure to citizens and the availability of data and indicators that provide an individualized view of fiscal management is relatively recent. Therefore, we seek to identify which socioeconomic characteristics of brazilian municipalities appear to have the greatest influence on the FIRJAN Fiscal Management Index (IFGF) for the more than five thousand Brazilian municipalities, as well as to identify homogeneous groups of cities based on such characteristics, using the K-Means method for clustering. Among the main conclusions, we highlight that Brazilian cities are very homogeneous and face the same social vulnerabilities and that the average level of municipal investment does not significantly differ between groups, even when we compare groups with greater socioeconomic disparities.